Tracking Reactivation of Location Information during Memory Strategies: Insights from Eye Movements - Ruhi Bhanap; Lea M. Bartsch; Agnes Rosner (Journal of Cognition)
Memory strategies such as visual imagery and rehearsal are widely reported by participants as means to enhance recall. Their underlying mechanisms are thought to differ. Visual imagery is believed to engage both visual and spatial aspects of memoranda, while rehearsal is thought to reactivate only the item-specific information, excluding spatial information. In this study, we employed the Looking at Nothing (LAN) effect – in which individuals make eye movements towards the original location of the memorized item during retrieval – to investigate the reactivation of spatial location in both visual imagery and rehearsal. Our findings demonstrate that LAN occurs with both strategies, indicating that spatial information is reactivated during rehearsal as well. Notably, we observed higher immediate as well as delayed memory performance with visual imagery compared to rehearsal. However, the amount of LAN observed for both these strategies remained the same. To further explore whether these differences in the amount of LAN and memory performance were driven by a modulation of the strength of long-term memory (LTM) traces we introduced proactive interference (PI) in a second experiment. PI is known to impact LTM traces, while leaving working memory (WM) intact. While PI led to a decline in WM for visual imagery, the amount of LAN remained the same. These results indicate that visual imagery and rehearsal both reactivate location information and additionally, visual imagery drives eye movements and memory benefits through distinct mechanisms.